Service Quality, Price and Consumer Switching Behaviour in The Nigerian Telecommunication Industry, Moderating Effect of Value Added Services on the Relationship - Dauda, Mohammed; Ibrahim Jatau, Babuji (British Journal of Marketing Studies, 2023)
The main objective of this study is to examine the Determinants of consumer switching behaviour in Nigerian telecommunication industry, the moderating role of value added services. Data were collected from the students of tertiary institutions in Borno state, North eastern Nigeria using a cross-sectional study design. The study adopted Kriejcie and Morgan (1970) rule of thumb and arrived at 382 respondents and questionnaires were distributed and collected through the personally-administered method. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to test the study hypothesis. This study finds that Value Added Services have significant influence on consumer switching behaviour, while Service Quality and Price have no significant influence on consumer switching behaviour, it also finds that value added services does not moderate the relationship between service quality, price and consumer switching behaviour. The results of this study provide important insights to managers, mobile operators and researchers to further understand the factors that influence consumers to switch from one service provider to another in the Nigerian telecommunication industry. Mobile operators should concentrate on factors like value added services so as to attract more customers to their network.